The Impact of Quality of Work Life on Employee Performance in Corporate Sector - E Sajitha (IJRDO - Journal of Business Management, 2024)
The quality programs initiated by the organizations enhance the ability of the employees to regulate their work behaviors, thought processes, and emotions. Productivity, improved product value and excellence are only possible when employees are taken care to the utmost. Quality is indeed a generic need in the public domain and has to be addressed in all dimensions of life. A healthy working environment results in job satisfaction, improves organizational performance, and complements efficacy with innovativeness. Beyond all of these, it ensures the workforce to lead a fullest, happiest and meaningful life adding value to the organization with work life balance. A study has been conducted among corporate employees located in Hyderabad. The quantitative and qualitative data has been collected using random sampling technique from the sample size of 100 employees working in private companies. A structured questionnaire and personal interview allowed the researcher to gather the ample information. The study aims to understand the level of satisfaction of the corporate employees towards the components of Quality of work life. The study also strives to understand the correlation of certain dimensions like working environment, compensation & benefits, and career growth & development components of QWL impacting the employees overall performance. With the help of statistical tools it is observed that there is a significant impact, and there exists correlation among selected dimensions and employees overall performance. A positive work environment with employee centric policies and practices, cultural alignment, high rewarding environment fostering the open communication and appreciation, empowering team members and inclusivity for employee growth acknowledging their efforts are noteworthy to enhance the quality of work life of employees and the performance extraordinarily.